‘I felt like a human being’—An exploratory, multi‐method study of refugee involvement in the development of mental health intervention research - Warner, Georgina; Baghdasaryan, Zaruhi; Osman, Fatumo; Lampa, Elin; Sarkadi, Anna (Health expectations : an international journal of public participation in health care and health policy, 2021)
Background Great advancements have been made in patient and public involvement (PPI), including the development of guidance on how to conduct, report and evaluate PPI. Despite these efforts, the evidence base remains relatively weak. A substantive methodological development is required. This is particularly important for vulnerable groups within society, for whom PPI can be challenging but has the potential to play a transformative role in shaping research. Objectives To describe the group dynamic characteristics and immediate impact of PPI from the user representatives’ perspective in a case study of refugee involvement in the development of mental health intervention research. To pilot and methodologically appraise the Active Involvement of Users in Research Observation Schedule and Questionnaire. Design The Active Involvement of Users in Research Observation Schedule and Questionnaire were administered together with a focus group discussion. Setting ‘Refugee Advisors’ were involved in the development of a randomized controlled trial protocol evaluating a brief group intervention for refugee children experiencing symptoms of post‐traumatic stress in Sweden. Results The multi‐method approach demonstrated good feasibility. There were clear examples of how the advisors influenced research development. The advisors described a perceived impact on the research, equality and acceptance, and knowledge gain. A sense of appreciation and empowerment was also interpreted. However, potential issues relating to the relevance of contributions and use of an interpreter were identified. Discussion and conclusion The methodological approach piloted in this study offers a promising, rigorous way to evaluate PPI. The research tools require further refinement and validation.